Passive Sociopathy - Ilievski, Naum; Angelina Ilievska (European Journal of Multidisciplinary Studies, 2020)
In the domain of complex relational phenomena and social behaviors, passive sociopathy (N. Ilievski) is described as a form of inadequate behavior with a negative impact not only in the immediate, but also in the wider social context as a global psycho-social phenomenon. This dysfunctional pattern is an indicator of psycho-social distortion with unproductive to extremely passive and risky behavior. Analysis and description of this phenomenon through the three psychological components: emotional, cognitive, and behavioral, in correlation with exogenous factors and influences, from the aspect of Christian psychotherapy and the model of Transactional analysis. The practice of Christian psychotherapy sets prayer as a central point of the FCP method in cultivating empathy as a dimension of emotional intelligence through which an emotionally healthy base is built in the person with adequate prosocial behaviors. Contemporary man, faced with the challenges of modern trends – in which the mass media of hyper information plays an important role – is flooded with negative information that changes the threshold of his perception and sensitivity to the level of discount, emotional dullness, to extreme insensitivity as the main characteristic of passive sociopathy.
Keywords: passive sociopathy, Christian psychotherapy, transactional analysis, prayer, prosocial behavior